UPAYA PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI PENGEMBANGAN KARIR, KETERLIBATAN KERJA DAN CARIER PLATEAU PADA DINAS KESEHATAN KABUPATEN KONAWE - Imron Imron (Jurnal Riset Bisnis Indonesia, 2014)
The purpose of this research is to determine the effect of career development, job involvementand carrier plateau on the performance of human resources at the Department of Health Konawe.Data were collected by distributing questionnaires to respondents that are all employees of theDepartment of Health Konawe. Samples from this study were 87 employees of the Department ofHealth Konawe who made the object of research by using purposive random sampling stratifield.This study uses descriptive analysis to determine the characteristics of respondents and descriptiveof the respondents for each indicator variable. The instrument used to test the relationship betweenvariables using SEM methods and analysis techniques of PLS (Partial Least Square). The resultsshowed that: (1) career development has negative significant effect on the carrier plateau, (2) Jobinvolvement has negative significant effect on the carrier plateau, (3) Carrier plateau has negativesignificant effect on the performance of human resources, (4) career development has positivesignificant effect on the performance of human resources, and (5) Job involvement has positivesignificant effect on the performance of human resources.Keywords: career development, job involvement, carrier plateau and human resources performance.